O sagrado portátil: perspetivas antropológicas - Teixeira, Alfredo (Lusitania sacra, 2016)
Presented in the context of an international colloquium on portable Bibles of the twelfth and thirteenth centuries, this essay proposes the theoretical mapping of four access routes to the morphology of the sacred: the originating sacred, the memorable sacred, the diffuse sacred and the graphomotor sacred. In this multi-scope itinerary, we specifically seek a comprehensive approach to the portability qualities of the sacred, confronting theoretical models and examples of the historiographic and ethnographic archive.